Debt Overhang or Debt Irrelevance? : Revisiting the Debt-Growth Link - Cordella, Tito (IMF Working Papers; Working Paper, 2005)
Do Highly Indebted Poor Countries (HIPCs) suffer from a debt overhang? Is debt relief going to improve their growth rates? To answer these important questions, we look at how the debt-growth relationship varies with indebtedness levels and other country characteristics in a panel of developing countries. Our findings suggest that there is a negative marginal relationship between debt and growth at intermediate levels of debt, but not at very low debt levels, below the 'debt overhang' threshold, or at very high levels, above the 'debt irrelevance' threshold. Countries with good policies and institutions face overhang when debt rises above 15-30 percent of GDP, but the marginal effect of debt on growth becomes irrelevant above 70-80 percent. In countries with bad policies and institutions, overhang and irrelevance thresholds seem to be lower, but we cannot rule out the possibility that debt does not matter at all.